The Realization of Interpersonal Meaning in the Report Text of the Undergraduate Students of Universitas Batanghari Jambi - Vrika, Renggi; Mujiyanto, Januarius; Suwandi, Suwandi (English Education Journal, 2019)
In interpersonal meaning, language is used to see the relationship between the speaker/writer with the listener/reader. Using interpersonal meaning to analyze written text is useful to see how the writer gives information and suggestion to the reader. This study investigated the interpersonal meaning realizing in the report text that is 354 clauses from 20 texts written by the undergraduate students. It used the framework from the Systemic Functional Linguistics by Eggins (2004) and Halliday and Matthiessen (2014). This research is qualitative case study research because it focuses on the analysis or interpretation of the written material. It analyzes mood system, modality system, speech function and students’ mastery in writing report text. From the analysis, it found that mostly declarative mood realized in the report text, it is 334 clauses and it is categorized as statement in the speech function. In the modality system, the most type realized in the text is modalization type, it is 38 clauses. By analyzing report text using interpersonal meaning, it was found the students’ mastery in the writing skill. The are only some students did mistakes in writing some clauses. Therefore using interpersonal meaning to analyze text help to know the mastery of the students in writing and also can improve their skill. It can be said that interpersonal meaning also realize in the report text. The realization can be seen from the types of mood, modality and speech function that were found in the report text.